PENYELIDIKAN PELAKU USAHA PERHOTELAN PENERIMA TAMU YANG BERBUAT ASUSILA BERDASARKAN PERATURAN DAERAH NOMOR 5 TAHUN 2002 TENTANG KETERTIBAN UMUM DI KOTA PEKANBARU - Amna, Khairinil; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Morality deals with morals, ethics have been regulated in the legislation. Hospitality receptionbusinessmen who do immoral as it should have been regulated in sections 23, 24 and 26 of theregulation Area number 5 year 2002 Regarding public order Pekanbaru. With the rise of thehospitality trade reception which do this very wanton need for investigation by Police teachers 'Praja Pekanbaru in order to prosecute these thoroughly in order to catch every offender whoallegedly received hospitality business guests do the applicable rules as sacrilegious. The presenceof law enforcement law enforcement can be expected to perform tasks correctly so that it can createsecurity and comfort for the community. The purpose of writing this thesis, namely; First, thehospitality trade investigation front desk who do immoral based on applicable local 5-year 2002Number of public order in the city of Pekanbaru. Second, the factors restricting the hospitalitytrade investigation front desk who do immoral based on applicable local 5-year 2002 Number ofpublic order in the city of Pekanbaru. Third, efforts are being made to overcome the obstacles inthe investigation of the hospitality trade front desk who do immoral based on applicable local 5-year 2002 Number of public order in the city of Pekanbaru.This type of research can be classified in types of juridical sociological research, because inthis study the authors direct research on the location or place that is examined in order to give acomplete and clear picture of the problems researched. This research was conducted in the city ofPekanbaru, while population and the sample is the entire parties relating to issues that areexamined in this study, the data source used, the primary data, secondary data and data collectiontechniques, tertier the data in this study with observation, questionnaire, interview and the study oflibrarianship.From the results of the research there are three basic issues that can be inferred. First,investigations carried out several actions i.e., receive reports and complaints, seek information andevidence as well as collecting and processing information. Second, the factors restricting inquiry,factors from law enforcement, the means and facilities, as well as a factor of masayarakat. Third,improving the mentality of law enforcers, adding personnel and increase public participation. Theauthor's suggestion, first, investigations optimally. Second, it can carry out its duties andauthorities which are supposed to be best. Third, the society participated in overseeing theunexpected hospitality reception businessmen who do wanton and reported to law enforcement.Keywords: Investigation - Crime - Wanton - Hotel